GERAKAN OPINI DIGITAL #TRUEBEAUTY PADA TWITTER UNTUK PEMERAN FILM ADAPTASI KOMIK WEBTOON - Lady Joanne Tjahyana (Universitas Teuku Umar, 2020)
Digital Movement of Opinion (DMO) using hashtag #TrueBeauty on Twitter was conducted by the fans of True Beauty as one of the most popular Webtoon’s comic. The fans gave their opinion about the perfect cast for the movie adaption of the comic. The objective of this research is to analyse the network that was formed by the DMO of #TrueBeauty. The method that had been used was social network analysis and the datasets mining was done using Netlytic. This research indicates that fans as the actors of the DMO were spreaded widely across the network and not centralized into certain dominant actors. The actors was divided into different clusters and every cluster has its own characteristics based on different locations and cultures. Therefore the role of influencers or dominant actors in every cluster is very important to deliver opinions with a style that suits every community. Moreover, text analysis found that film industry should pay attention to social media opinion, because many of the opinion were reflects the original desires of every fan without any intermediaton from any parties.